Трав'янистий покрив лісового ландшафтного району дендропарку “Тростянець” - Nesterenko, V.P.; Ilyenko, A.A.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The phytocenotic characteristics and floristic composition of herbaceous vegetation of forest landscape region of dendropark Trostyanets are shown.